Shakespeare - Hart, J. author. aut Link
XII, 268 p.
Keywords: In this stunning reinterpretation of Shakespeare s works, Jonathan Hart explores key topics such as love, lust, time, culture, and history to unlock the Bard s brilliant fictional worlds. From an in-depth look at the private and public myths of love in the narrative poems, through an examination of time in the sonnets, to a discussion of gender in the major history plays, this book offers close readings and new perspectives. Delving into the text and context of a wide range of poems and plays, Hart brings his wealth of experience to bear on Shakespeare s representation of history.